The relationship between service quality, trust, and consumer satisfaction on consumer loyalty - Novia Ridatul Artika; Titi Rapini; Titis Purwaningrum (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
Consumer loyalty is an essential thing in the world of marketing. A company is also required to cultivate its competitive advantage through various innovative, creative, and efficient efforts so that it becomes a choice of existing consumers, and it is hoped that, in the end, they will be loyal to the company. This study aims to determine service quality, trust, and consumer satisfaction on consumer loyalty at beauty salon raf beauty art Ponorogo. The sample is a consumer who has had treatment at the RAF Beauty Art Beauty Salon, using a purposive sampling technique and a sample of 100 respondents. The analysis used in this study uses multiple linear regression analysis using the SPSS 26 program to show that perceived trust partially and customer satisfaction have a positive and significant influence on consumer loyalty.